Impacts of human activities on coastal ecological environment during the rapid urbanization process in Shenzhen, China. (15th March 2018) - Yi, Lin; Chen, Jinsong; Jin, Zhifeng; Quan, Yiming; Han, Pengpeng; Guan, Shujing; Jiang, Xiaoli
Abstract: How human activities impact on coastal ecosystem during rapid urbanization is one of the hot spots in the coastal management study. In this paper, we comparatively evaluate changes in the positive and the negative ecological elements of Shenzhen's coastal zone in the rapid urbanization process to understand impacts of human activities. The positive and the negative ecological elements divided by built of classification based on extracted land uses from multi-source remote sensing images and land-use degree index. Then landscape indexes such as AWMSI, ED, PSSD, PSCOV at the class level and CONNECT, SHEI at both class level and landscape level were used to reveal spatial and temporal differentiation of impacts of human activities on ecological elements. Results revealed that impacts of human activities on coastal ecosystem were stronger in west coast than that in east coast, and environmental protection awareness of government began to enhance from 2000, whereas the ecosystem health didn't become better. Future urbanization plans about coastal zones need to consider the ecological benefit of the landscape pattern from both a local and global point of view. This method can contribute to the sustainable management of other coastal zones. Highlights: A human activities' impact assessment was carried on Shenzhen's coastal zone with rapid urbanization, China. The new ecological elements classification can show differences in intensities of human activities. Environmental protection awareness increased in the rapid urbanization of Shenzhen's coastal zone. Coastal management in Shenzhen need to consider landscape patterns of ecological elements.